Samerna & Herr Erik : En postkolonial studie om kolonisationen av Sápmi genom en prästs ögon - Bredgaard, Linus (Linnéuniversitetet, Institutionen för kulturvetenskaper (KV), 2018)
The purpose of this study is to examine the colonisation of Sápmi though the works of a local priest, by the name of Eric Grape. To do so, this study uses postcolonial theory when analysing the content of the works by Grape. Eric Grape was a priest active in the Lappmarks of northern Sweden in the early nineteenth century and who wrote articles for the Swedish Royal Academy of Sciences. The focus of the study is the othering of the Saami people and their culture, and the colonial production of knowledge that Grape produced about the Saami. Othering is a term by Edward Said and it is about the constructed difference between “we” the European culture and people regarded as the “other”. This term, the study argues, can also be applied when studying the colonial encounters between the Saami and Swedish colonial actors such as Grape. The main result of this study is that Grape portrays the Saami as different and more primitive than the Swedish settlers that occupy the northen part of Sweden, he describes the Saami as childish.